Validation of a Pan-fungal polymerase chain reaction (PCR) assay for the detection and identification of medically important fungi in a diagnostic laboratory - Ntuli, Sindile Venessa (Division of Medical Microbiology, 2018)
The laboratory diagnosis of fungal infection is complicated, based on the microscopic detection, culture isolation, and detection of serological response. In recent years, there has been an increase in the utilization of molecular diagnostic techniques for the detection and accurate identification of fungal pathogens. This was a laboratory accuracy study evaluating the performance of a selected pan-fungal PCR using 70 previously identified reference fungal isolates. The DNA yield and purity of three different DNA extraction methods was assessed, using 6 representative fungal isolates. The ZR Fungal/Bacterial DNA MicroPrep™ produced a median concentration of 17.28 ng/μl,which was significantly higher (p value = 0.0079) than the MagNA pure LC DNA Isolation Kit III and QIAamp DNA Mini Kit, which produced median yields of 11.08ng/μl and 3.54 ng/μl, respectively. The selected pan-fungal PCR was optimized PCR and successfully performed on 62 of the 70 reference isolates. A selection of 56 amplicons were submitted for DNA sequence determination. Of all the sequences queried on the NCBI and Ribosomal Development Project (RDP) databases, 95/111(86%) were concordant with the results obtained from the reference laboratory. Study findings have shown that the selected pan-fungal PCR, coupled with DNA sequence analysis is an excellent diagnostic tool for the identification of medically relevant fungi. This assay, in combination with conventional culture, is useful for the rapid and accurate identification of fungal isolates. Future work will involve evaluating the utility of this assay for the detection and identification of medically relevant fungi in deep tissue biopsies.